2022
DOI: 10.1007/s11356-022-24333-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of water ecological environment in watersheds: a case study of the Yangtze River Economic Belt, China

Abstract: The Yangtze River Economic Belt, as an inland economic zone with global influence, has shown a trend of prosperous economic development in recent years. In 2020, the total population of the Yangtze River Economic Belt accounted for nearly 50% of China's total population, and the GDP has reached 471,580 billion yuan. With economy developing, water pollution, resource depletion and many other environmental problems continue to emerge. Steady state of water ecological environment is an important part of ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…As an important water environment performance assessment indicator, the water quality rating data reflect the comprehensive water quality of a specific river or lake. At the same time, China's Ministry of Ecology and Environment issued the "Program for Ranking the Water Environment Quality of National Surface Water Assessment Sections in Prefecture-level and Above Cities (Trial)", which clearly stipulates that the ranking of the water environment quality of each city is determined in accordance with the water quality level [17]. The water environment is gradually becoming an important reference indicator for the performance assessment of local governments.…”
Section: Plos Onementioning
confidence: 99%
“…As an important water environment performance assessment indicator, the water quality rating data reflect the comprehensive water quality of a specific river or lake. At the same time, China's Ministry of Ecology and Environment issued the "Program for Ranking the Water Environment Quality of National Surface Water Assessment Sections in Prefecture-level and Above Cities (Trial)", which clearly stipulates that the ranking of the water environment quality of each city is determined in accordance with the water quality level [17]. The water environment is gradually becoming an important reference indicator for the performance assessment of local governments.…”
Section: Plos Onementioning
confidence: 99%
“…Leng et al [ 18 ] showed the prevalence of PFASs midstream through water monitoring and analysis. Xu et al [ 19 ] conducted a comprehensive evaluation of the water ecological environment of the Yangtze River Economic Belt using a weighted rank and ratio model and an adversarial explanatory structure model, and found that water ecology has not yet reached a safe and stable state. Bi et al [ 20 ] examined the spatial and temporal changes in water supply, soil conservation, and water purification services in the Yangtze River Economic Belt from 2000 to 2018 using the InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs) model and suggested that ecological conservation be tailored to local conditions.…”
Section: Introductionmentioning
confidence: 99%